Competitor Analysis Using Business Intelligence for Product Innovation - Sumalatha, M. R.; Velmurugan, Kavin; Yuvaraj, Santhosh; Swarnalatha, M. R. (Transactions on Engineering and Computing Sciences, 2023)
Competitor analysis and product innovation are important requirements for both strategic and operational management. The competitive characteristics of reviewers’ comments are used to innovate and improve the product. The primary objective is to develop a comprehensive framework that intelligently learns from competitors’ data and suggests innovative methods to aid the product to become a market leader with the help of artificial intelligence. The goal of this project is to create a model for analyzing and understanding the competitor’s performance, its strengths, weakness, methods through various ways such as competitive attributes from consumers’ perspectives, observation of the competitors’ adverts etc. This model is expected to help in business decisions, a decision support system is created and help in the innovation of their product. The proposed system consists of the following modules: Trust computation module to compute the amount of trust in a product and its advertisements, Information storage module to store and process the video and image advertisements required efficiently, Video analytics module to derive key information from the filtered videos based on trust score, a Decision support system to make intelligent decisions for determining the multi-objective parameters for product innovation.